Evaluation of functional capacity for exercise in children and adolescents with sickle cell disease through the Six Minute Walk Test - Sandro V. Hostyn; Werther B. de Carvalho; Cíntia Johnston; Josefina A.P. Braga (Brazilian Society of Pediatrics, 2013)
Objective: to evaluate lung functional capacity (FC) for physical exercise in children and adolescents with sickle cell disease (SCD) through the six-minute walk test (6MWT). Method: a cross-sectional prospective study was performed to evaluate the FC of 46 patients with SCD through the 6MWT. The following parameters were assessed: heart rate (HR), respiratory rate (RR), peripheral pulse oxygen saturation (SpO2), peak expira- tory flow (PEF), blood pressure (systolic and diastolic), dyspnea, and leg fatigue (modi- fied Borg scale) at rest, in the end of the test, and ten minutes after the 6MWT. The total distance walked was also recorded. For statistical analysis, the parametric varia- bles were analyzed using the paired Student's t-test, analysis of variance (ANOVA), and Bonferroni multiple comparisons, with a significance level set at p ≤ 0.05. Results: the 46 patients were aged age 9.15 ± 3.06 years, presented baseline Hb of 9.49 ± 1.67 g/dL, and walked 480.89 ± 68.70 m. SCD diagnosis was as follows: group 1- HbSS (n = 20)/HbSβ0-thalassemia (n = 3) and group 2 - HbSC (n = 20)/HbSβ+-thalassemia (n = 3). Regarding total distance walked, patients in group 1 walked a shorter distance than patients in group 2 (459.39 ± 57.19 vs. 502.39 ± 73.60 m; p = 0.032). There was no statistical difference regarding PEF in the three moments of evaluation. The SpO2 in ambient air and SpO2 with O2 differed between groups 1 and 2 (p < 0.001 vs. p = 0.002), as well as the RR (p = 0.001). Conclusion: these patients showed a lower FC for exercise than that predicted for the age range in the literature. Patients diagnosed with HbSS/Sβ0-thalassemia had a lower performance in the test than those with HbSC/Sβ+-thalassemia regarding total distance walked, RR, and SpO2 after the 6MWT.